Regional trade policy cooperation and architecture in East Asia - Siow Yue Chia (Asian Development Bank Institute (ADBI), 2010)
The global financial and economic crisis has affected East Asia mainly through the trade channel. The region remains heavily dependent on export markets in Europe and North America through both direct exports to these destinations and indirect exports via the export of parts and components to other East Asian countries, particularly the People's Republic of China, which are then assembled and exported as final goods to Europe and North America. The need to rebalance growth in East Asia in the post-crisis era requires measures to strengthen domestic demand and emphasize intra-regional demand. Production networks have been integrating East Asia and this integration process is being hastened by the rapid growth of regional and bilateral trade and economic agreements since the late 1990s. The trigger point for regionalism in East Asia appears to be the 1997-1998 Asian financial crisis, and regionalism is being accelerated by the dismal outlook for the Doha Development Round, the economic rise of the People's Republic of China and India, and the ongoing global financial crisis. Proposals on regional trade architecture include Association of Southeast Asian Nations (ASEAN)+3 and ASEAN+6 for East Asia, the Free Trade Area of the Asia Pacific, and an extension of the Trans-Pacific Strategic Economic Partnership. The case for a new regional trade architecture includes improved competitiveness and economic dynamism from a large integrated market; increased intra-regional flows of trade, investment, and human resources; expansion and deepening of production networks; a rebalancing of growth towards regional demand; and a stronger and cohesive voice in international fora and organizations. Challenges include the pressures of protectionism in an economic recession, the question of whether there is a common political vision, the existence of multiple and overlapping free trade agreements with the accompanying problem of the noodle bowl, and the wide development gap among the region's economies.
Keywords: F13; F15; 330; Freihandelszone; Handelsregionalismus; Internationale wirtschaftspolitische Koordination; ASEAN-Staaten; Ostasien